Tablet Splitting in Elderly Patients with Dementia: The Case of Quetiapine - Roberta Ganzetti; Serena Logrippo; Matteo Sestili; Alessandro Caraffa; Marco Cespi; Giuseppe Pelliccioni; Paolo Blasi; Giulia Bonacucina (MDPI AG, 2021)
Quetiapine is an atypical antipsychotic approved for treating schizophrenia, bipolar depression, and mania but is frequently used in an off-label manner to control the behavioral and psychological symptoms of dementia in elderly patients with dementia. Due to the need to personalize doses for elderly patients with dementia, quetiapine tablet manipulation is widespread in hospital settings, long-term care facilities, and patient homes. The aim of this study was to assess the impact of the different splitting techniques on quetiapine fumarate tablets by analysing the obtained sub-divided tablets and to discuss compliance with the European Pharmacopoeia limits on whole and split tablets. Quetiapine fumarate tablets of two dose strengths were taken at random (in a number able to assure a power of 0.8 during statistical comparison) and were split with a kitchen knife or tablet cutter. The weight and the drug content were determined for each half tablet. The obtained data were compared to the European Pharmacopoeia limits. The differences between the different splitting techniques were statistically tested. Data showed that split tablets, independently of the dose strength and the technique employed, were not compliant with the European Pharmacopoeia specifications for both entire and subdivided tablets in terms of weight and content uniformity. Thus, such a common practice could have potential effects on treatment efficacy and toxicity, especially when also considering the fragility of the elderly target population in which polypharmacotherapy is very common. These results indicate a compelling need for flexible quetiapine formulations that can assure more accurate dose personalization.